2021
DOI: 10.1021/acsnano.1c00263
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Dependent Morphological Transitions of Bottlebrush Block Copolymer Particles: Experiments and Simulations

Abstract: The molecular weights and chain rigidities of block copolymers can strongly influence their self-assembly behavior, particularly when the block copolymers are under confinement. We investigate the self-assembly of bottlebrush block copolymers (BBCPs) confined in evaporative emulsions with varying molecular weights. A series of symmetric BBCPs, where polystyrene (PS) and polylactide (PLA) side-chains are grafted onto a polynorbornene (PNB) backbone, are synthesized with varying degrees of polymerization of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 68 publications
0
33
0
Order By: Relevance
“…In addition, this small value of Δγ explains the selective positioning of the Au@Azo0.8 NPs on the PS/P2VP interface that was observed in the cross-sectional TEM images of Figure S6d. It is noted that when Δγ is sufficiently small, the perpendicular orientation of the BCPs relative to the particle surface is thermodynamically more stable compared with the parallel-oriented BCPs. , Additionally, spherical confinement of BCPs within an emulsion droplet imposes an additional entropic penalty on the bending of the copolymer domains, making the perpendicular BCP orientation more favorable. , The distinct increase of γ Au@Azo0.8+PS/CTAB under UV irradiation from 4.19 to 5.48 mN m –1 was attributed to the polar cis-Azo ligands on the Au@Azo0.8 NPs formed after photoisomerization. , When visible light was sequentially applied, γ Au@Azo0.8+PS/CTAB decreased back to 4.28 mN m –1 , affording a larger Δγ = 1.38 mN m –1 and demonstrating the excellent reversibility. The same trend was also confirmed at higher homopolymer concentrations (i.e., 16.7 mg mL –1 ) of PS 51k and P2VP 50k in CF, respectively (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, this small value of Δγ explains the selective positioning of the Au@Azo0.8 NPs on the PS/P2VP interface that was observed in the cross-sectional TEM images of Figure S6d. It is noted that when Δγ is sufficiently small, the perpendicular orientation of the BCPs relative to the particle surface is thermodynamically more stable compared with the parallel-oriented BCPs. , Additionally, spherical confinement of BCPs within an emulsion droplet imposes an additional entropic penalty on the bending of the copolymer domains, making the perpendicular BCP orientation more favorable. , The distinct increase of γ Au@Azo0.8+PS/CTAB under UV irradiation from 4.19 to 5.48 mN m –1 was attributed to the polar cis-Azo ligands on the Au@Azo0.8 NPs formed after photoisomerization. , When visible light was sequentially applied, γ Au@Azo0.8+PS/CTAB decreased back to 4.28 mN m –1 , affording a larger Δγ = 1.38 mN m –1 and demonstrating the excellent reversibility. The same trend was also confirmed at higher homopolymer concentrations (i.e., 16.7 mg mL –1 ) of PS 51k and P2VP 50k in CF, respectively (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…It is noted that when Δγ is sufficiently small, the perpendicular orientation of the BCPs relative to the particle surface is thermodynamically more stable compared with the parallel-oriented BCPs. 65,66 Additionally, spherical confinement of BCPs within an emulsion droplet imposes an additional entropic penalty on the bending of the copolymer domains, making the perpendicular BCP orientation more favorable. 65,67 The distinct increase of γ Au@Azo0.8+PS/CTAB under UV irradiation from 4.19 to 5.48 mN m −1 was attributed to the polar cis-Azo ligands on the Au@Azo0.8 NPs formed after photoisomerization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the length of the backbone has been recently shown to influence the formation of the final ordering within the particle. [167] It was reported that increasing the backbone length will increase the entropic penalty of stretching or bending the BBCPs into curved lamellae, which will eventually overwhelm the enthalpic contribution from stabilizing the droplet interface. This results in axial stacking of the lamellae into an ellipsoidal particle becoming preferred for high MW BBCPs or for very small droplets, where the effects of the confinement geometry are amplified.…”
Section: Concentric Multilayersmentioning
confidence: 99%
“…Comb copolymers, where two or more dissimilar types of side chains as macromers are grafted to a linear polymer backbone with a certain macromer sequence, have attracted much interest recently owing to their intriguing self-assembly behaviors [ 24 , 25 , 26 , 27 , 28 , 29 ]. Analogous to TBC having a triblock sequence based on monomeric units, comb copolymers can also have triblock sequence based on macromer units ( Figure 1 ), which envisions its use for a novel type of molecular composites or thermoplastic elastomer [ 30 , 31 , 32 ] with a number of additional advantages such as more variety of options for functional design of macromers as a reinforcing component.…”
Section: Introductionmentioning
confidence: 99%